ANALISIS SEMIOTIK TERHADAP GAME â€œPIRATES AHOY!â€ - RIKI HIMAWAN MULYADI; ELIZABETH WIANTO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Pirates Ahoy! is an online game developed and released by Playfish, a subsidiary of Electronic Arts from London in July 2010. This pirates game theme could stimulate players to play it continuously, because itâ€™s competitive value and easy to play. This game is interesting to analize from semiotic perspective inspite of its theme about violent life, Pirates Ahoy! visualization appears in a simple design and friendly look. Playing it online through social media, the players could satisfy their desire to globally exist without space and time boundaries.Â Keywords: competitive; online game; semiotic; sign; social media